2018
DOI: 10.1073/pnas.1719785115
|View full text |Cite
|
Sign up to set email alerts
|

Skin microbiota and allergic symptoms associate with exposure to environmental microbes

Abstract: SignificanceUrban, Westernized populations suffer extensively from noncommunicable diseases such as allergies. However, the overlapping effects of living environment and lifestyle are difficult to separate. Intriguingly, also our fellow animals, dogs, suffer from analogous diseases. Therefore, we suggest that pet dogs, sharing their environment and lifestyle with humans but having a comparatively simple life, provide a valuable model for understanding origins of noncommunicable diseases. We show that living en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
89
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(97 citation statements)
references
References 40 publications
7
89
0
1
Order By: Relevance
“…Taken together, our data support the notion that differences in the effects of cat and dog ownership might be a consequence of a cat being a marker of high allergen exposure, whereas the protective effect of dog exposure can be mediated through changes in the skin microbiome. 50 The findings of the current study confirm our previous observation of the changing nature of the association between early-life exposures and sensitization with time and the crucial importance of longitudinal analyses. 15 Furthermore, they raise fundamental questions about the current approach to replication in genetic and gene-environment studies because the timing of the assessment of outcomes can critically affect the results of different studies investigating genes, the environment, and their interactions.…”
Section: Discussionsupporting
confidence: 90%
“…Taken together, our data support the notion that differences in the effects of cat and dog ownership might be a consequence of a cat being a marker of high allergen exposure, whereas the protective effect of dog exposure can be mediated through changes in the skin microbiome. 50 The findings of the current study confirm our previous observation of the changing nature of the association between early-life exposures and sensitization with time and the crucial importance of longitudinal analyses. 15 Furthermore, they raise fundamental questions about the current approach to replication in genetic and gene-environment studies because the timing of the assessment of outcomes can critically affect the results of different studies investigating genes, the environment, and their interactions.…”
Section: Discussionsupporting
confidence: 90%
“…In both studies, the order of the most common phyla found in affected ears was the same: Firmicutes was the most common, followed by Actinobacteria and Proteobacteria . Although a preliminary study found that the microbial community did not appear to be influenced by individual factors and environment in dogs, several other studies indicate that these factors do affect cutaneous microbiota . This may explain any difference in findings between our two studies .…”
Section: Discussionmentioning
confidence: 49%
“…First is geographical location, because the dogs sampled in the previous study were presumably recruited from within the state of Texas, USA, whereas the dogs in our study were recruited from the Province of Ontario, Canada. Another study found that the bacterial microbiota of dogs was influenced by their environment and lifestyle . Therefore, it is likely that climate and other geographical factors could influence the composition of the otic mycobiota.…”
Section: Discussionmentioning
confidence: 99%